2009
DOI: 10.5551/jat.1875
|View full text |Cite
|
Sign up to set email alerts
|

Role of Rho/Rho-Kinase and NO/cGMP Signaling Pathways in Vascular Function Prior to Atherosclerosis

Abstract: Aim: Atherosclerosis is a cardiovascular disease; however, there is little information on signal transduction for vascular function in the early stage of atherosclerosis. In this work, we investigated the role of Rho/Rho-kinase and nitrogen oxide (NO)/cyclic GMP (cGMP) signaling pathways in the aorta prior to atherosclerosis. Methods: Tension, the expression of RhoA protein, Rho-kinase activity and the cGMP level were measured using endothelium-intact or -denuded aorta prepared from apolipoprotein E-deficient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…Rho/ROCK pathway is substantially involved in inflammatory and arteriosclerotic arterial lesions in animals and humans (reviewed in references 16,168,169). Multiple studies in experimental models involving fasudil 170172 and other ROCK inhibitors 173,174 have demonstrated that ROCK is a critical contributor to the inflammatory atherosclerotic process. ROCK inhibitors lead to up-regulation of eNOS and reduced endothelial dysfunction, 174,175 decreased vascular cell contraction, proliferation and migration, 174,176,177 decreased vascular oxidative stress, 178 decreased vascular inflammation, macrophage infiltration and foam cell formation, 171,173 and reduced arterial intima-medial thickness and atherosclerosis plaque formation.…”
Section: Rock In Cardiovascular Diseasesmentioning
confidence: 99%
“…Rho/ROCK pathway is substantially involved in inflammatory and arteriosclerotic arterial lesions in animals and humans (reviewed in references 16,168,169). Multiple studies in experimental models involving fasudil 170172 and other ROCK inhibitors 173,174 have demonstrated that ROCK is a critical contributor to the inflammatory atherosclerotic process. ROCK inhibitors lead to up-regulation of eNOS and reduced endothelial dysfunction, 174,175 decreased vascular cell contraction, proliferation and migration, 174,176,177 decreased vascular oxidative stress, 178 decreased vascular inflammation, macrophage infiltration and foam cell formation, 171,173 and reduced arterial intima-medial thickness and atherosclerosis plaque formation.…”
Section: Rock In Cardiovascular Diseasesmentioning
confidence: 99%
“…Each strip of the aorta was placed in a 5-mL organ bath containing normal Krebs solution (Na 137.4, K 5.9, Mg 2 1.2, Ca 2 2.6, HCO3 15.5, H2PO4 1.2, Cl 134, glucose 11.5 mM; pH 7.4) bubbling with 95% O2 and 5% CO2. After an equilibration period of 60 minutes, the mechanical activity was measured via isometric recording under a resting tension of 300 mg 20) . PE was added in increments to study the concentration-dependent effects.…”
Section: Measurement Of Tensionmentioning
confidence: 99%
“…In fact, p38 activation is an intermediary of pro-inflammatory-induced tissue damage and the pathophysiology of heart disease (Kaiser et al, 2004; Kerkela and Force, 2006; Clark et al, 2007) and has been the target of therapeutic intervention strategies (Marber et al, 2010). Similarly, ROCK involvement in CVD comorbidities including hypertension (Mukai et al, 2001; Seko et al, 2003; Moriki et al, 2004), atherosclerosis (Rekhter et al, 2007; Mori-Kawabe et al, 2009; Wu et al, 2009) and cardiac hypertrophy and heart failure (Higashi et al, 2003; Satoh et al, 2003; Fukui et al, 2008; Phrommintikul et al, 2008), has been the focus of directed therapeutics. These efforts highlight the significance of these signaling pathways in CVD progression.…”
Section: Discussionmentioning
confidence: 99%